An Ultra-Wide Range D-Shaped Fiber SPR Sensor with a Nanostructure of Gold–MoS2 and Sodium for the Simultaneous Measurement of Refractive Index and Temperature - Xinglian Lu; Xiantong Yu; Jun Zhou; Min Chang; Dunke Lu (Sensors)
Refractive index (RI) and temperature (T) are both critical environmental parameters for environmental monitoring, food production, and medical testing. The paper develops a D-shaped photonic crystal fiber (PCF) sensor to measure RI and T simultaneously. Its cross-sectional structure encompasses a hexagonal-hole lattice, with one hole selectively filled with toluene for temperature sensing. By coating the D-shaped surface of the PCF with a metal film and a MoS2 film, the refractive index-detection channel is formed. Numerical results demonstrate that RI and T can be reflected in the same spectrum, without any interference caused by the two parameters with each other. At an environmental RI of 1.26–1.38, its maximum RI sensitivity is up to 5400 nm/RIU. At a temperature of 20–80 °C, its temperature sensitivity reaches −1.2 nm/°C. This design allows for a broad operational spectrum and an extensive measurement range, which makes it particularly suitable for applications requiring low-RI detection. Moreover, the resonance strength of the sensor is significantly enhanced by introducing a two-dimensional material MoS2 on the D-surface. Specifically, it reaches 195,149 dB/m when RI = 1.34 at 30 °C. This is much higher than that of most previous studies, and the requirements for inspection equipment can be lowered in this case. These results are essential for progress in simultaneously detecting RI and T.